Institutional Audit of Pediatric and Adolescent Malignancy in Nepal - Sharma, Krishna Sagar; Panthi, Sabita; Pradhananga, Kishor; Shrestha, Bhaktaman (Nepalese Journal of Cancer, 2020)
Background: There have been no records of the incidence of pediatric malignancy recorded in Nepal until recently. The aim of this study is to analyze the cases of pediatric malignancy reported in 2006 in order to find out the relative frequency and geographical distribution of childhood malignancy throughout Nepal. Methods: All the data for 2006 were collected from the Hospital-based Cancer Registry of Nepal (B P Koirala Memorial Cancer Hospital Registry Programme). All the cases included in the report were analyzed for geographical distribution, age, sex and relative frequency of the various types of childhood malignancies. The cancers were all classified according to the International Classification of Childhood Cancer (ICCC) and separated into 12 major groupings. Result: A total 343 children and adolescents from seven tertiary care hospitals located in the western, middle and eastern regions of Nepal were registered in the Hospital-based Cancer Registry Program of Nepal. A majority of the patients were from the eastern and mid-eastern regions. The others were from the western, far-western and mid-western regions. Very few of them were from the far-western and mid-western regions. The males had a higher reported rate of malignancies than the females, 60% vs. 40%. The adolescent population (13-19 years old) had 43% of the malignancies: a significant number. Leukemia (33%), lymphoma (18%) and bone tumors (13%) were the first, second and third most common cancers among the 12 groups. The number of reported cases has increased each year from 2003 to 2006. Discussion: The Hospital-based Cancer Registry was started in 2003. At that time not much attention was given during the collection of data to making note of the different variables. The incidence of pediatric malignancies has not been known till now. This study shows that the relative frequencies of pediatric malignancies and leukemiaare the same as in western countries. Knowledge of the national incidence is necessary in order to make proper policies for the treatment of children with cancer and for research in the field of pediatric oncology. Brain tumors are the second most common cancer in developed countries but in our study it is the fifth most common malignancy: 20% Vs 5%. We have a higher percentage of bone tumors 10% vs. 5% unlike other developed countries where population based registry data are available.